MANFAAT METODE MASSAGE EFFLEURAGE DAN AROMA TERAPI LAVENDER SERTA METODE BONAPACE UNTUK MENURUNKAN SKALA NYERI IBU BERSALIN KALA 1 - Nailufar Firdaus; Iin Setiawati; Norma Farizah Fahmi (STIKES NGUDIA HUSADA MADURA, 2021)
The phenomenon that occurs at this time, was found some during the first stage of the active phase, many mothers who gave birth experience severe pain. so the mother chose caesarean section even without a clear indication of normal delivery. Non-pharmacological efforts to reduce pain are by providing effleurage massage therapy with lavender aromatherapy and bonapace method therapy. This technical collaboration is very good, so we are interested in doing community service. Community service is carried out by providing counseling then teaching mothers and families as well as midwives the effleurage technique with lavender aroma therapy and bonapace method therapy techniques. What is expected that mothers who give birth will not experience severe labor pain so that mothers who give birth choose normal delivery rather than cesarean delivery.